Chronic pelvic pain - Philip Zinn (South African Family Practice)
Chronic pelvic pain is defined as pain in the pelvis lasting for more than six months (some say three). The pain may be experienced in any of the structures of the pelvis, including the gynaecological organs; the lower urinary and gastrointestinal tract; and the vascular, neural and musculoskeletal systems. The pain can be continual, cyclical, provoked or unprovoked, and is frequently multifocal. A woman who complains of painful sex, for example, may also report vulvovaginal pain and dyspareunia; bladder frequency, urgency and suprapubic pain, as well as irritable bowel symptoms. Although an initiating event is sometimes described, such as an episode of severe “thrush” or cystitis, or following pelvic surgery or childbirth, this initial insult may be long forgotten and no longer relevant. Vulvodynia, endometriosis, bladder pain syndrome and irritable bowel syndrome are common causes of chronic pelvic pain in women but are often misdiagnosed and poorly managed.